Android-Based Educational Game Development Learning Media Material for SMK Programming Algorithm Structure - Deny Prasetyo; Faridatus Shofiyah; Yulaikha Mar'atullatifah; Suyahman; Muhammad Anwar Fauzi (Ali Institute of Research and Publication, 2026)
This study aims to develop and evaluate an Android-based educational game as a learning medium for programming algorithm structures for Vocational High School (SMK) students. The research method used is research and development with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. Product evaluation was conducted through validation by media experts and material experts, as well as trials with students consisting of individual, small group, and large group tests. Research data were collected using assessment questionnaires and student response questionnaires, then analyzed descriptively using percentages. This study focused on formative evaluation to test the validity and practicality aspects of the media. Inferential testing of learning impacts became suggestions for further research development. The validation results showed that the developed educational game was in the very feasible category. In addition, the results of the student response questionnaire showed positive perceptions of the clarity of the material, ease of use, and student involvement in learning programming algorithms. These findings indicate that Android-based educational games have the potential to be supporting learning media in helping SMK students understand the structure of programming algorithms.